Challenging Conceptions 2023
DOI: 10.1093/oso/9780197648315.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Kinship, and Affiliation of Children Born of War in Patriarchal Northern Uganda

Abstract: This chapter explores the importance of kinship for children born of war among the Langi ethnic group of northern Uganda. Based on the author’s extensive on ethnographic research, she explores the experiences of ten children conceived in the Lord’s Resistance Army (LRA), who after exiting the LRA joined their maternal families and communities in Lango. The author finds that these children could not benefit directly from the policies that regulated the descent affiliation of newborns. First, by not invoking Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is important to explain that relocation to other places was not unique to Teso sub-region only. The same occurs in Acholi (Atim et al, 2018;Bergmans, 2017;Stewart, 2017) and Lango (Apio, 2016) sub-regions. Using the argument of 'push and pull' factors in migration (Lee, 1966), the movement of these children and their mothers from their initial locations to others is influenced by unbearable circumstances in their first point of settlement and the anticipation that life in their destination could be much better.…”
Section: Children Born In Captivity As a Hidden Populationmentioning
confidence: 66%
“…It is important to explain that relocation to other places was not unique to Teso sub-region only. The same occurs in Acholi (Atim et al, 2018;Bergmans, 2017;Stewart, 2017) and Lango (Apio, 2016) sub-regions. Using the argument of 'push and pull' factors in migration (Lee, 1966), the movement of these children and their mothers from their initial locations to others is influenced by unbearable circumstances in their first point of settlement and the anticipation that life in their destination could be much better.…”
Section: Children Born In Captivity As a Hidden Populationmentioning
confidence: 66%
“…(see for example Apio, 2016;Baines, 2017;Porter, 2017;Stewart, 2017;Atim et al, 2018, p. 68). Some of the mothers reported that upon return, their families had been killed or displacedthe result of which was life in poverty, and inability to fend for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mothers reported that upon return, their families had been killed or displacedthe result of which was life in poverty, and inability to fend for their children. In as much as some of their relatives wanted their "children" (young mothers) to return to them, their having had children born from the "bush" impacted negatively on the way CBOW have been received as children of the enemies (also see Apio, 2016;Mukasa, 2017;Stewart, 2017). Research has also revealed how the mothers' lives are clouded with shame and agony of being associated with the LRA (Liebling and Baker, 2010;Mukasa, 2017;Liebling, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With this, Adok testifies to the centrality of marriage for legitimacy and belonging. 16 Without recognition in the paternal home, Adok is denied status, land, and the care that should be extended to women through marriage. 17 In her desire to identify and meet her children's paternal families, Adok seeks the truth of their origins.…”
mentioning
confidence: 99%